NARRATIVAS DE PROFESSORAS QUE ENSINAM MATEMÁTICA NOS ANOS INICIAIS ACERCA DA EXPERIÊNCIA CONSTITUÍDA EM UM GRUPO COLABORATIVO - LUCIENE SOUSA BASSO (2023)
This Doctoral Thesis presents data and directions of a Master's research, linked to the Postgraduate Program in Mathematics Education (PPGEduMat) of the Federal University of Mato Grosso do Sul (UFMS), research line "Teacher Training and Curriculum". We aimed to analyze the contribution of the "Group of Collaborative Practices in Mathematics Education in the Early Years" (GPCEMai/UFMS), in the reconstitution of the knowledge of teachers who participated in the group that was active in the city of Naviraí-MS (Brazil). We took as a basis for the investigation the verification that, gradually, from the results of previous investigations, there has been research on the formation of teachers in pedagogy courses and how the degree in question is insufficient in relation to the space/time destined to the mathematical contents for the first years of schooling, data that raises the necessity of actions of continuous formation. To this end, the study in question is qualitative in nature and points to results that can generate contributions to theoretical and methodological advances in the field of education and, in particular, mathematics education. For the production of data, we have resorted to narrative research, and specifically to the narrative interview from the perspective of Fritz Schütze, in an attempt to locate the meanings and experiences of the collaborating teachers (Sandra and Cleuza) for rethinking their experiences based on the contribution they observe in their practices when experiencing moments of collaboration in GPCEMai/UFMS. In view of the possibilities of problematizing the theme in question, the fieldwork advances in the sense of better perceiving the effects of long-term collaborative work, a perspective that is still little recurrent in the works of the field, and how teachers have shown acceptance of this type of training (university-school partnership) and value practices of continuous training in which teachers develop professionally while also learning together in the field of mathematics education in the early years. From the biographies narrated, the importance of the collaborative group was perceptible for the teachers who gave us the interview. For them, the experience constituted in the collaborative space contributed to the re-signification of their knowledge in the following points 1) expansion of the didactic-pedagogical repertoire, given the nature of the study actions, planning, task validation, development and reflection of the ways of acting; 2) knowledge of the theoretical production on how to approach and promote children's mathematical thinking, which strengthens the foundations of pedagogical action; and, finally, 3) change of attitude by providing more confidence to explore mathematical concepts supported by the collectivity resulting from the group. KEY WORDS: Narratives. Collaborative group. Early childhood mathematics education.